91.0k views
10 votes
Help please, not sure how to do this....

Help please, not sure how to do this....-example-1
User Cjlarose
by
5.5k points

1 Answer

4 votes

Answer:


4√(2b)

Explanation:


√(98b)-√(72b)+√(18b)

Apply radical rule
√(ab) =√(a) √(b):


\implies √(98)√(b) -√(72)√(b) +√(18)√(b)

Factor out common term
√(b):


\implies √(b)(√(98) -√(72)+√(18))

Rewrite 98, 72 and 18:


\implies √(b)(√(49 \cdot 2) -√(36 \cdot 2)+√(9 \cdot 2))


\implies √(b)(√(49)√(2) -√(36)√(2)+√(9)√(2))


\implies √(b)(7√(2) -6√(2)+3√(2))

Factor out common term
√(2):


\implies √(b)√(2)(7 -6+3)


\implies √(b)√(2)(4)


\implies 4√(2b)

User Cpinamtz
by
4.9k points